Practice Based Approaches to Supporting the Work Related Wellbeing of Frontline Care Workers in Care Homes: A Scoping Review - Lucy Johnston; Cari Malcolm; Lekaashree Rambabu; Jo Hockely; Susan Shenkin (Journal of Long-Term Care, 2021)
The COVID-19 pandemic has reinforced the need to ensure that strategic and operational approaches to retain high quality, resilient frontline care home workers are informed by context specific, high quality evidence. A targeted scoping review asked the question: what is the current evidence base for practice based approaches that support the work related wellbeing of frontline care workers in care homes? The aim was to map the extent and nature of the care home specific evidence base and identify key interventions, theories and practice components. Thirty studies were included. Thematic synthesis identified the following four key themes: Culture of Care; Content of Work; Connectedness with Colleagues and Characteristics and Competencies of Care Home Leaders. Evidence for best practice in supporting care home work related wellbeing is extremely limited, of variable quality and lacks generalisability. Overall, the evidence base was found to be theoretically, empirically and practically fragmented and as a result, there is at present, no consensus about which areas of work related wellbeing, if addressed, would have most impact. Compounding this lack of coherence, is the limited specificity of the studies. The implicit nature of the current evidence base is also a result of the limited number of care home specific studies, their variable focus and quality, and the marked heterogeneity in the outcome measures and related indicators used by different studies. This scoping review has distilled important areas that warrant further exploration and research from within a very limited and diffuse evidence base, for example, the potential of Person Centred Care (PCC) as a protective mechanism for both resilience and retention and the more nebulous concepts of support and job satisfaction. The insight provided by the scoping review will inform future strategic and operational approaches to retain high quality, resilient frontline care home workers. However, the evidence base must move from its current state of implicitness to one of detailed explication. Future research should focus on high quality, adequately powered and co-designed intervention studies to determine which practice-based approaches are of most importance, how they ‘work’ or ‘don’t work’ alone or in combination to support the work related wellbeing of frontline care workers in care homes.